731 Predicting 6-month modified Rankin Scale score in stroke patients (Balneo and PRM Research Journal, 2024)
The study aimed to identify predictors of 6-month outcomes in acute ischemic stroke (AIS) patients using the modified Rankin Scale (mRS). A prospective observational cohort study was conducted on 277 AIS patients admitted to the Neurology Departments of Cluj-Napoca Emergency County Clinical Hospital between December 2020 and July 2021. After excluding those lost to follow-up or who withdrew due to COVID-19 concerns, 121 patients were followed for six months. Data collected included demographic details, clinical assessments (including NIHSS and mRS scores), laboratory tests, and imaging results. The study found significant differences between patients with mild/moderate disability (mRS 0-3) and those with severe disability (mRS 4-5) at six months. Age, heart failure, NIHSS score, resistin levels, C-reactive protein, and lesion volume were significantly associated with worse outcomes. Multivariate logistic regression revealed that heart failure was an independent predictor of severe disability, increasing the risk by over seven times. Specific clinical and biochemical markers at admission may be able to predict long-term functional outcomes in AIS patients, which may inform individualized patient management and rehabilitation strategies.